Core-loaded T-Nb2O5-coated Si skin-core structure carbon fiber, preparation method thereof and application of core-loaded T-Nb2O5-coated Si skin-core structure carbon fiber in negative electrode of lithium ion battery
By using the core-carrying carbon fibers covered with Si in the negative electrode material of lithium-ion battery, the problem of volume expansion and poor conductivity of silicon materials is solved, the cycle stability and rate performance of the battery are improved, and high energy is achieved Density lithium-ion battery.
Patent Information
- Application Number
- CN202411273568.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-09
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing lithium-ion battery negative electrode material silicon, due to volume expansion and poor conductivity, has poor cycle stability and rate performance, making it difficult to meet the needs of high energy density and high performance batteries.
The carbon fiber with a core-carrying T-Nb2O5 coated Si is used to construct the T-Nb2O5 coated layer by hydrothermal method and a carbon fiber network is constructed using coaxial electrospinning technology to limit the volume expansion of silicon and improve conductivity.
It significantly improves the cycle stability and rate performance of lithium-ion batteries, improves the electrochemical reactivity and conductivity of electrode materials, and extends the battery life of electric equipment.
Smart Images

Figure CN119121460A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a skin-core structured carbon fiber with a core-loaded T-Nb2O5 coated with Si, a preparation method thereof, and an application thereof in a negative electrode of a lithium-ion battery. Background Art
[0002] With the continuous depletion of traditional fossil fuels, energy shortages and environmental pollution have emerged. Consequently, alternative energy sources have been widely used in recent years. Among them, lithium-ion batteries, with their high energy density and long cycle life, have become the most popular new energy storage device. With technological advancements and social development, the application of lithium-ion batteries has gradually expanded from small electronic devices to electric vehicles (EVs), unmanned aerial vehicles (UAVs), aerospace, and other fields. Therefore, the future development goal is to achieve more efficient and lightweight energy storage.
[0003] The higher the energy density of a battery, the more energy it can carry under the same mass, which has a great impact on the endurance performance and lightweight level of electric equipment. According to the plans of China, the United States, Japan and other countries, the energy density of lithium batteries will reach 300Wh kg by 2020. -1 , reaching 400Wh kg in 2025 -1 , reaching 500Wh kg in 2030 -1 , and mass production will be achieved in 2025-2030. The theoretical specific capacity of commercial graphite anode is only 372mAh g -1 , it is difficult to meet the demand for high-performance batteries in the future.
[0004] Silicon is one of the most abundant elements on earth, due to its high theoretical specific capacity (3579mAh g -1 ) and low lithium insertion potential, making it a strong candidate material for improving the energy density of lithium-ion batteries. However, there are still several problems: 1) The large volume expansion coefficient (~300%) generates huge stress during the charge and discharge process, causing silicon particles to break and pulverize; 2) Silicon is a typical semiconductor material with poor electrical conductivity ((10 -5 -5 -10 S cm -1 ), the lithium ion diffusion rate is low (1.9×10 -14 cm 2 s -1 ), which severely limits the rate performance and cycle stability of silicon negative electrode materials.
[0005] In response to the above problems, the current solution of researchers is usually to composite silicon with other materials in different forms, such as carbon materials, metal compounds, etc. Patent CN106848276A discloses a modification method for coating titanium dioxide on the surface of silicon particles, which takes advantage of the small volume change of titanium dioxide during the lithium insertion and removal process to limit the volume expansion of silicon particles, but cannot improve the problem of poor conductivity of silicon. Patent CN108963201A prepares silicon-carbon nanofiber negative electrodes by electrospinning. The carbon fiber structure can provide a conductive network and a self-supporting skeleton, improve conductivity and provide a large number of lithium insertion and removal channels, but the invention adopts a uniaxial spinning experimental method. Part of the silicon powder is exposed on the fiber surface, which will cause a large volume expansion effect, and even pulverize and fall off the electrode, causing the electrode structure to be destroyed.
[0006] During the charge and discharge process, lithium ions in T-Nb2O5 are charged and discharged by embedding / de-embedding the crystal lattice, with little volume change. Wrapping it on the silicon surface can play a good confinement role. At the same time, T-Nb2O5 has a complex tunnel structure, providing abundant surface redox reaction sites and fast ion diffusion channels, which makes it have a better pseudocapacitive effect, and therefore has better performance at high-rate charge and discharge. Summary of the Invention
[0007] Based on the technical problems in the prior art, the present invention designs and develops a skin-core structured carbon fiber with core-loaded T-Nb2O5 coated Si. The purpose of the present invention is to solve the problem of limiting the volume expansion of silicon by utilizing the stability of the skin-core structured carbon fiber with core-loaded T-Nb2O5 coated Si, and at the same time solves the problem of significantly improving the cycle stability and rate performance of existing materials while improving conductivity and ensuring high discharge specific capacity.
[0008] The present invention also designs and develops a method for preparing a skin-core structured carbon fiber with core-loaded T-Nb2O5 coated Si. After constructing a T-Nb2O5 coating layer on the surface of nano-silicon particles by a hydrothermal method, the T-Nb2O5 coated Si is used as the core layer to construct a skin-core structured carbon fiber network by coaxial electrospinning, thereby solving the problem of preparing a skin-core structured carbon fiber with core-loaded T-Nb2O5 coated Si.
[0009] The present invention also designs and develops a skin-core structured carbon fiber with core-loaded T-Nb2O5 coated with Si for use in the negative electrode of a lithium-ion battery, solving the problem of improving the energy density of the lithium-ion battery.
[0010] The technical solution provided by the present invention is:
[0011] A method for preparing a core-loaded T-Nb2O5-coated Si-shell carbon fiber comprises the following steps:
[0012] Step 1: After preparing the piranha solution, add nano-silicon powder, stir at room temperature and then freeze-dry to obtain surface hydroxylated nano-silicon powder;
[0013] Step 2: After preparing a hydrated niobium oxalate solution and a polyvinyl pyrrolidone solution, respectively, the surface hydroxylated nano-silicon powder is added to the polyvinyl pyrrolidone solution and stirred to obtain a first solution; the hydrated niobium oxalate solution is added to the first solution and stirred to obtain a second solution; the second solution is subjected to a hydrothermal reaction, freeze-dried, and calcined under an inert gas atmosphere to obtain a niobium pentoxide-coated nano-silicon structure;
[0014] Step three, dissolve polyacrylonitrile and degas to obtain a third solution, dissolve polyvinyl pyrrolidone and polymethyl methacrylate, add the niobium pentoxide-coated nano-silicon structure and stir to obtain a fourth solution, add the third solution and the fourth solution into the coaxial electrospinning syringe respectively, push and collect the fiber membrane, vacuum dry and perform pre-oxidation treatment, and then perform carbonization treatment to obtain the core-loaded T-Nb2O5-coated Si skin-core structure carbon fiber.
[0015] Preferably, in the step 2, 1 wt% to 5 wt% of niobium oxalate hydrate is dissolved in deionized water to prepare the niobium oxalate hydrate solution;
[0016] Dissolving 5 wt% to 20 wt% of polyvinyl pyrrolidone in deionized water to prepare the polyvinyl pyrrolidone solution; and
[0017] 1 wt% to 10 wt% of the surface hydroxylated nano-silicon powder is added to the polyvinyl pyrrolidone solution.
[0018] Preferably, in step 2, the temperature of the hydrothermal reaction is 200° C. and the time is 12 h; and
[0019] The calcination temperature is 700° C. and the calcination time is 2 h.
[0020] Preferably, in the step 3, 10 wt% to 20 wt% of polyacrylonitrile is dissolved in 2-methylformamide and then degassed to obtain the third solution; and
[0021] After dissolving 10 wt% to 20 wt% of polyvinyl pyrrolidone and 1 wt% to 10 wt% of polymethyl methacrylate in 2-methylformamide, 20 wt% to 50 wt% of the niobium pentoxide-coated nano-silicon structure was added and stirred to obtain a fourth solution.
[0022] Preferably, in the step 3, 10 wt% to 20 wt% of polyacrylonitrile is dissolved in 2-methylformamide until the solution becomes clear and transparent light yellow, and then the solution is allowed to stand at room temperature for degassing to obtain the third solution; and
[0023] 10wt%-20wt% of polyvinyl pyrrolidone and 1wt%-10wt% of polymethyl methacrylate are dissolved in 2-methylformamide, and the solution is allowed to stand at room temperature until it becomes clear and transparent. Acetone is then added and stirred at room temperature. 20wt%-50wt% of the niobium pentoxide-coated nano-silicon structure is then added and stirred to obtain a fourth solution.
[0024] Preferably, the third solution and the fourth solution are added to the coaxial electrospinning syringe respectively, the high voltage is set to 14KV to 18KV, and the propulsion speed of the third solution is 0.7 to 1.0 mL h -1 The propulsion speed of the fourth solution is 0.1-0.3 mL h -1 , the drum collection speed is 300rpm and the collection distance is 15cm.
[0025] Preferably, in step 3, the vacuum drying process is performed at a temperature of 60° C. and for a time of 4 hours;
[0026] The pre-oxidation treatment is performed at a temperature of 230° C. for 2 hours; and
[0027] The temperature of the carbonization treatment is 700° C. and the time is 2 h.
[0028] A carbon fiber with a skin-core structure having a core loaded with T-Nb2O5 and coated with Si is prepared using the method for preparing the carbon fiber with a skin-core structure having a core loaded with T-Nb2O5 and coated with Si.
[0029] The invention discloses an application of a carbon fiber with a skin-core structure in which a core is loaded with T-Nb2O5 and coated with Si in a negative electrode of a lithium-ion battery, and uses the carbon fiber with a skin-core structure in which a core is loaded with T-Nb2O5 and coated with Si.
[0030] Preferably, the core-loaded T-Nb2O5 coated Si skin-core structured carbon fiber is cut and assembled into a lithium half-cell.
[0031] The beneficial effects of the present invention are:
[0032] 1. The skin-core structured carbon fiber Si with core-loaded T-Nb2O5 coated Si prepared by the preparation method of the present invention has a short rod-shaped T-Nb2O5 coating structure on its surface. T-Nb2O5 has excellent structural stability. Therefore, this coating structure can not only limit the volume expansion of silicon during the charge and discharge process, but also increase the specific surface area of the material, provide more reactive sites, and improve the electrochemical reaction activity of the electrode material. At the same time, T-Nb2O5 has excellent pseudocapacitive performance, which can greatly improve the rate performance of the electrode material.
[0033] 2. The surface of the core-core structured carbon fiber with T-Nb2O5 coated with Si prepared by the preparation method of the present invention and further using coaxial electrospinning technology is relatively smooth and has no exposed particles. This skin-core structure not only limits the volume expansion of Si during the charge and discharge process, but also prevents Si from falling off the electrode, which is beneficial to maintaining the integrity of the electrode structure. At the same time, the interconnected carbon fiber conductive network uniformly distributed along the fiber axis provides a continuous electron transmission channel, improves the conductivity of the electrode material, and also provides a fast ion diffusion channel, thereby improving the reaction rate of the electrode material under high-rate charge and discharge;
[0034] 3. When the core-loaded T-Nb2O5-coated Si skin-core structure carbon fiber provided by the present invention is used in the negative electrode of a lithium-ion battery, while ensuring a high discharge specific capacity, the cycle stability and rate performance are significantly improved, which is beneficial to improving the energy density of the battery, extending the life of electric equipment, and further promoting the popularization of electric vehicles, thereby reducing the use of fossil fuels and carbon emissions. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 a is the XRD pattern of Si / T-Nb2O5@C-CCNF prepared in the embodiment of the present invention, Figure 1 b is the Raman spectrum of Si / T-Nb2O5@C-CCNF prepared in the embodiment of the present invention;
[0036] Figure 2 a is the XPS spectrum of Si / T-Nb2O5@C-CCNF prepared in the embodiment of the present invention, Figure 2 b is the HRXPS spectrum of C1s of Si / T-Nb2O5@C-CCNF prepared in the embodiment of the present invention, Figure 2 c is the HRXPS spectrum of N1s of Si / T-Nb2O5@C-CCNF prepared in the embodiment of the present invention, Figure 2 d is the HRXPS spectrum of O 1s of Si / T-Nb2O5@C-CCNF prepared in the embodiment of the present invention, Figure 2e is the HRXPS spectrum of Si 2p of Si / T-Nb2O5@C-CCNF prepared in the embodiment of the present invention, Figure 2 f is the HRXPS spectrum of Nb3d of Si / T-Nb2O5@C-CCNF prepared in the embodiment of the present invention;
[0037] Figure 3 a is a TEM schematic diagram of Si / T-Nb2O5-P prepared in the embodiment of the present invention, Figure 3 b is a schematic partial enlarged TEM image of Si / T-Nb2O5-P prepared in the embodiment of the present invention, Figure 3 c is the HRTEM image of Si in the Si / T-Nb2O5-P material prepared in the embodiment of the present invention, Figure 3 d is the HRTEM image of T-Nb2O5 in the Si / T-Nb2O5-P material prepared in the embodiment of the present invention, Figure 3 e is a HAADF image of the Si / T-Nb2O5-P material prepared in the embodiment of the present invention, Figure 3 f is the HAADF image of Si / T-Nb2O5-P material Si prepared in the embodiment of the present invention, Figure 3 g is the HAADF image of Si / T-Nb2O5-P material O prepared in the embodiment of the present invention, Figure 3 h is a HAADF image of Nb in Si / T-Nb2O5-P material prepared in the embodiment of the present invention;
[0038] Figure 4 a is a schematic SEM plan view of Si / T-Nb2O5@C-CCNF prepared in the embodiment of the present invention, Figure 4 b is a SEM schematic diagram of a single Si / T-Nb2O5@C-CCNF fiber prepared in the embodiment of the present invention. Figure 4 c is an EDS diagram of the distribution of C element in a single Si / T-Nb2O5@C-CCNF fiber prepared in the embodiment of the present invention. Figure 4 d is an EDS schematic diagram of the distribution of N elements in a single Si / T-Nb2O5@C-CCNF fiber prepared in the embodiment of the present invention. Figure 4 e is an EDS schematic diagram of the distribution of O element in a single Si / T-Nb2O5@C-CCNF fiber prepared in the embodiment of the present invention. Figure 4 f is an EDS diagram of the Si element distribution in a single Si / T-Nb2O5@C-CCNF fiber prepared in the embodiment of the present invention. Figure 4g is an EDS schematic diagram of the distribution of Nb elements in a single Si / T-Nb2O5@C-CCNF fiber prepared in an embodiment of the present invention;
[0039] Figure 5 a is the EIS test curve of the Si / T-Nb2O5@C-CCNF electrode prepared in the embodiment of the present invention, Figure 5 b is the equivalent circuit diagram of the Si / T-Nb2O5@C-CCNF electrode prepared in the embodiment of the present invention before and after cycling;
[0040] Figure 6 a is a schematic diagram of the GITT of the Si / T-Nb2O5@C-CCNF electrode sheet prepared in the embodiment of the present invention, Figure 6 b is a schematic diagram of the lithium ion diffusion rate of the Si / T-Nb2O5@C-CCNF electrode sheet prepared in the embodiment of the present invention;
[0041] Figure 7 a is the Si / T-Nb2O5@C-CCNF electrode sheet prepared in the embodiment of the present invention at 0.2A g -1 Schematic diagram of long cycle performance test under current density, Figure 7 b is the Si / T-Nb2O5@C-CCNF electrode sheet prepared in the embodiment of the present invention under 0.5Ag -1 Schematic diagram of long cycle performance test under current density and Figure 7 c is the Si / T-Nb2O5@C-CCNF electrode sheet prepared in the embodiment of the present invention at 1Ag -1 Schematic diagram of long cycle performance test under current density, Figure 7 d is the Si / T-Nb2O5@C-CCNF electrode sheet prepared in the embodiment of the present invention on 2Ag -1 Schematic diagram of long cycle performance test under current density;
[0042] Figure 8 a is a schematic diagram of the rate performance test of the Si / T-Nb2O5@C-CCNF electrode sheet prepared in the embodiment of the present invention, Figure 8 b is a schematic diagram of the discharge capacity of the Si / T-Nb2O5@C-CCNF electrode sheet prepared in the embodiment of the present invention at different rates;
[0043] Figure 9 a is the Si / T-Nb2O5@C-CCNF negative electrode material prepared in the embodiment of the present invention at 0.1mV S -1 Schematic diagram of CV test under sweep speed, Figure 9b shows the Si / T-Nb2O5@C-CCNF negative electrode materials prepared in the embodiment at 0.2 mV S -1 , 0.4mV S -1 , 0.6mV S -1 , 0.8mV S -1 , 1mV S -1 Schematic diagram of CV test under sweep speed, Figure 9 c is a schematic diagram of the fitting curves of log v and log i of the positive / negative peaks in multi-scan CV. Figure 9 d is the contribution percentage of diffusion control and surface control at different scan rates, Figure 9 e is a schematic diagram of capacitance contribution at different scan rates. DETAILED DESCRIPTION
[0044] The present invention will be described in further detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0045] The present invention provides a method for preparing a skin-core structured carbon fiber with a core-loaded T-Nb2O5 coated with Si, which specifically comprises the following steps:
[0046] Step 1: Surface hydroxylation treatment of nano-silicon powder: After preparing piranha solution, add nano-silicon powder, stir at room temperature and then freeze-dry to obtain surface hydroxylated nano-silicon powder;
[0047] Step 2: Preparation of niobium pentoxide-coated nano-silicon structure: After preparing a hydrated niobium oxalate solution and a polyvinyl pyrrolidone solution, respectively, labeled as solution N and solution P, the surface hydroxylated nano-silicon powder is added to solution P. After stirring, solution N is added to the above solution, and the mixture is hydrothermally reacted and freeze-dried. The mixture is calcined under an inert gas atmosphere to obtain a niobium pentoxide-coated nano-silicon structure, labeled as Si / T-Nb2O5-P.
[0048] Step 3. Preparation of niobium pentoxide-coated silicon skin-core structure carbon nanofibers: dissolve polyacrylonitrile and degas to obtain a third solution, marked as solution A; dissolve polyvinyl pyrrolidone and polymethyl methacrylate, add niobium pentoxide-coated nano-silicon structure and stir to obtain a fourth solution, marked as solution B, add solution A and solution B into the coaxial electrospinning syringe respectively, push and collect the fiber membrane, vacuum dry and pre-oxidize, and then carbonize to obtain core-loaded T-Nb2O5-coated Si skin-core structure carbon fiber, marked as Si / T-Nb2O5@C-CCNF.
[0049] In another embodiment, in step one, the method further includes adding 10wt%-20wt% nano-silicon powder (60-100nm), stirring at room temperature for 30-60min, washing by centrifugation with deionized water for 3-5 times, and then freeze-drying to obtain surface hydroxylated nano-silicon powder.
[0050] In another embodiment, in step 2, the following steps are further included:
[0051] Step 1: 1wt%-5wt% hydrated niobium oxalate (C 10 H5NbO 20 ) and 5wt%-20wt% PVP (polyvinyl pyrrolidone) were dissolved in deionized water, marked as solution N and solution P, respectively, and stirred at room temperature until clear and transparent;
[0052] Step 2: Add 1 wt%-10 wt% nano-Si(OH-) to solution P, sonicate for 30-60 min, stir for 1-3 h, then add solution N to the above solution, stir at room temperature for 1-2 h, and sonicate for 1 h;
[0053] Step 3: Transfer it to a polytetrafluoroethylene liner and carry out a hydrothermal reaction at 200°C for 12 hours. After the reaction is completed, the product is centrifuged and washed 3-5 times with deionized water, and then freeze-dried. The dried product is calcined in a tubular furnace under an argon atmosphere with the parameters set to 700°C for 2 hours. The calcined product is labeled Si / T-Nb2O5-P.
[0054] In another embodiment, in step three, the following steps are further included:
[0055] Step 1: Dissolve 10wt%-20wt% PAN (polyacrylonitrile) in DMF (2-methylformamide), stir at 70°C for 4-6h, until the solution is clear and transparent with a light yellow color, then let it stand at room temperature for degassing, and mark it as solution A. Dissolve 10wt%-20wt% PVP (polyvinyl pyrrolidone) and 1wt%-10wt% PMMA (polymethyl methacrylate) in DMF (2-methylformamide), stir at 60°C for 3-4h, until the solution is clear and transparent, then let it stand at room temperature, add a small amount of acetone, stir at room temperature for 1-2h, add 20wt%-50wt% Si / T-Nb2O5-P to the above solution, ultrasonicate at room temperature for 90min, stir for 6-8h, and mark it as solution B;
[0056] Step 2: Solution A was used as the shell solution and solution B was used as the core solution. They were added into the two electrospinning syringes of the coaxial electrospinning machine respectively. The high voltage was set to 14KV-18KV and the shell propulsion speed was set to 0.7-1.0mL h. -1, the core layer advancing speed is 0.1-0.3mLh -1 , the drum collection speed is 300rpm and the collection distance is 15cm.
[0057] Step 3: The fiber membrane obtained by coaxial electrospinning was vacuum dried (60°C, 4h), then the fiber membrane was peeled off from the release paper and placed in a muffle furnace for pre-oxidation treatment (230°C, 2h). The pre-oxidized fiber membrane was placed in a tubular furnace and carbonized under an argon atmosphere (700°C, 2h). The carbonized product was labeled Si / T-Nb2O5@C-CCNF.
[0058] The present invention also provides a core-loaded T-Nb2O5 coated Si skin-core structure carbon fiber, which is prepared by the above preparation method and marked as Si / T-Nb2O5@C-CCNF.
[0059] The present invention also provides an application of a core-loaded T-Nb2O5-coated Si skin-core structured carbon fiber in a lithium-ion battery negative electrode. The Si / T-Nb2O5@C-CCNF fiber membrane is cut into discs with a diameter of d=12 mm. A 2032 battery shell is used to assemble the above-mentioned Si / T-Nb2O5@C-CCNF disc fiber negative electrode into a lithium half-cell according to the negative electrode shell-fiber negative electrode-Celgard2325 diaphragm-lithium sheet-gasket-spring-positive electrode shell.
[0060] Example
[0061] The present invention provides a method for preparing a skin-core structured carbon fiber with a core-loaded T-Nb2O5 coated with Si, which specifically comprises the following steps:
[0062] Step 1: Surface hydroxylation of nano-silicon powder: Prepare 10 mL of piranha solution, then add 1-2 g of nano-silicon powder (60-100 nm), stir at room temperature for 30 min, then centrifuge and wash with deionized water for 3-5 times and freeze-dry. The mixture is labeled as nano-Si(OH - );
[0063] Step 2: Preparation of niobium pentoxide-coated nano-silicon structure:
[0064] Step 1: 1 wt% hydrated niobium oxalate (C 10 H5NbO 20 ) and 6 wt % PVP (polyvinyl pyrrolidone) were dissolved in deionized water, marked as solution N and solution P, respectively, and stirred at room temperature until clear and transparent;
[0065] Step 2: 5wt% nano-Si(OH -) was added to solution P, ultrasonicated for 30 min, stirred for 1 h, and then solution N was added to the above solution, stirred at room temperature for 2 h, and ultrasonicated for 1 h;
[0066] Step 3: transfer it to a polytetrafluoroethylene liner and perform a hydrothermal reaction at 200°C for 12 hours. After the reaction is completed, the product is washed 3-5 times with deionized water by centrifugation, and then freeze-dried. The dried product is calcined in a tube furnace under an argon atmosphere with the parameters set at 700°C for 2 hours. The calcined product is labeled Si / T-Nb2O5-P;
[0067] Step 3: Preparation of niobium oxide-coated silicon skin-core carbon nanofibers:
[0068] Step 1: Dissolve 30 g of PAN (polyacrylonitrile) in 200 mL of DMF (2-methylformamide) and stir at 70°C for 4 h until the solution becomes clear and transparent with a light yellow color. Then, let it stand at room temperature for degassing, which is labeled as Solution A. Dissolve 10 g of PVP (polyvinyl pyrrolidone) and 5 g of PMMA (polymethyl methacrylate) in 100 mL of DMF (2-methylformamide), stir at 60°C for 3 h until the solution becomes clear and transparent, then let it stand at room temperature, add a small amount of acetone, and stir at room temperature for 1 h. Add 40 wt% Si / T-Nb2O5-P to the above solution, sonicate at room temperature for 90 min, and stir for 6 h. This is labeled as Solution B.
[0069] Step 2: Solution A was used as the shell solution and solution B was used as the core solution. They were added into the two electrospinning syringes of the coaxial electrospinning machine respectively. The high voltage was set to 14KV-18KV and the shell propulsion speed was 0.7mL / h. -1 , the core layer advancing speed is 0.1mLh -1 , the drum collection speed is 300rpm, and the collection distance is 15cm;
[0070] Step 3: The fiber membrane obtained by coaxial electrospinning is vacuum dried (60°C, 4h), then the fiber membrane is peeled off from the release paper and placed in a muffle furnace for pre-oxidation treatment (230°C, 2h), and the pre-oxidized fiber membrane is placed in a tubular furnace and carbonized under an argon atmosphere (700°C, 2h) to obtain a skin-core structured carbon fiber with core-loaded T-Nb2O5 coated with Si. The carbonized product is labeled Si / T-Nb2O5@C-CCNF.
[0071] The carbonized Si / T-Nb2O5@C-CCNF fiber membrane was cut into discs with a diameter of d = 12 mm, and the above Si / T-Nb2O5@C-CCNF disc fiber negative electrode was assembled into a lithium half-cell using a 2032 battery shell according to the negative electrode shell-fiber negative electrode-Celgard2325 separator-lithium sheet-gasket-spring-positive electrode shell.
[0072] Test Case
[0073] X-ray diffraction (XRD) testing can be used to analyze the crystal structure, chemical composition and crystallographic data of materials. It is an important method for determining the phase structure of samples in the disciplines of materials and chemistry. By irradiating the surface of the crystal to be tested with X-rays of a certain wavelength, under the action of X-rays with strong penetrating power, several layers of regularly arranged atomic planes in the crystal structure interfere with each other. According to the Bragg equation: 2d sinθ=nλ (d is the interplanar spacing, θ represents the angle of incidence, and λ is the wavelength of X-rays), different crystals will produce diffraction effects according to their own specific unit cell parameters, interplanar spacing and other parameters. By comparing the diffraction patterns collected at different angles with the peak positions and intensities in the PDF standard card, information such as the crystal structure and chemical composition of the material can be obtained. The instrument model used for the XRD test in this test example is Rigaku Mini Flex, which uses Cu target Kα rays (including Kα2, As a ray source, the collection range is 10-90°, the working voltage is 40KV, and the scanning speed is 10° / min.
[0074] Raman spectra analysis is based on the Raman scattering effect. When lasers of different wavelengths penetrate a sample, they can excite scattered light with a frequency different from the incident light. By collecting and analyzing the spectrum, information corresponding to the sample structure can be obtained. The principle is that high-energy lasers will excite the sample molecules, which will then transition to energy levels different from the ground state and produce scattering that is different from the incident laser frequency, forming a scattering spectrum related to molecular vibration and rotation. The instrument model used for the Raman test in this test example is the Renishaw InVia Reflex, with a laser wavelength of 523nm and a test range of 100 to 3000cm -1 .
[0075] X-ray Photoelectron Spectroscopy (XPS) is a simple and fast method for calibrating the elemental composition and chemical state of materials. It excites the electrons of atoms or molecules in the sample by irradiating the sample surface with monochromatic X-rays, collects the emitted photoelectron signals and records the kinetic energy they carry, and can analyze information such as their elemental composition and valence state. In addition, the number of photoelectrons of certain energies collected can be used to calculate the element content of the sample. The instrument model used for the XPS test in this test example is the AXIS Supra of Shimadzu Corporation of Japan, which uses an aluminum target as the X-ray emission source (hv=1486.6eV) to analyze the composition, valence state and chemical environment of the elements on the sample surface.
[0076] Scanning Electron Microscopy (SEM) is a test method that characterizes the surface morphology of a sample by scanning the surface of a material with a high-energy electron beam and collecting and amplifying the excited secondary electron signal. It is usually used in conjunction with an energy spectrometer. Energy dispersive X-ray Spectroscopy (EDS) analysis is a method of elemental analysis that collects and analyzes the energy differences of characteristic X-rays generated when electrons outside the sample nucleus are excited. It can characterize the type, content, and distribution of elements on the sample surface. In this test example, the SEM test fixed the sample on the sample stage with conductive glue, and the sample with poor conductivity was sprayed with gold. The instrument models used were Hitachi SU-70 and JSM-7800F.
[0077] A transmission electron microscope (TEM) uses a high-energy electron beam as a laser source and is an electron optical device with high resolution and high magnification. Its absorption imaging principle is as follows: a high-energy electron beam generated by an electron gun is accelerated and focused in a vacuum system, then projected onto an ultra-thin specimen. After colliding with atoms in the specimen, it changes direction and produces a specific solid angle scattering. Based on the scattering angle information, images of varying brightness and darkness can be obtained. After further magnification and focusing, a transmission electron image of the sample is ultimately obtained. High-resolution transmission electron microscopy (HRTEM) has higher resolution and can obtain lattice fringe images, dot matrix images, and single atom images of material microregions, allowing for more in-depth analysis of the structural morphology, crystallographic structure, and defect information of the material microregion. The instrument model used for the TEM test in this test example is the JEM-2100F produced by JEOL Ltd. The preparation method of TEM specimen is as follows: disperse the sample with anhydrous ethanol to obtain a uniform suspension, then take a small amount of the suspension and drop it on a molybdenum grid, irradiate it with an infrared lamp until the solvent evaporates, and obtain the specimen to be observed.
[0078] In this test, the Chi660E electrochemical workstation was used to perform EIS and CV tests on the assembled button cell. The impedance test frequency was set to 0.1-10 5 Hz, amplitude of 5 mV, and CV test sweep rate of 0.1 mV S -1 , the voltage range is 0.01-3V.
[0079] In this test example, the constant current intermittent titration test GITT was performed using the Xinwei battery test system. The specific method is: set the constant current charge and discharge program, the charge and discharge time is 30 minutes, the standby time is 5 hours, and the current size is set to 0.2A -1 , and further calculate the lithium ion diffusion coefficient D based on the test results Li+ .
[0080] In this test case, the Xinwei battery test system was used to test the -1 , 0.5Ag -1 , 1Ag -1 and 2Ag -1 The cycle stability and rate performance of the lithium half-cell were tested at a current density of .
[0081] like Figure 1As shown in a, it can be observed that Si / T-Nb2O5-P has obvious characteristic peaks in the X-ray diffraction pattern, among which the diffraction peak angles 2-Theta = 22.6°, 28.3°, 32.7°, 36.4°, 46.0°, 50.4°, and 58.5° correspond to (001), (180), (250), (181), (00 2), (321), (2160) crystal planes; the diffraction peak angles 2-Theta = 28.4°, 47.3°, 56.1°, 69.1°, 76.3°, and 88.0° correspond to the (111), (220), (311), (400), (331), and (422) crystal planes of cubic Si (PDF#27-1402), respectively, proving the successful preparation of T-Nb2O5-coated Si structure.
[0082] The XRD spectrum of Si / T-Nb2O5@C-CCNF shows that the peak around 2-Theta = 22.1° is an amorphous carbon peak, which comes from the carbonization of the outer layer PAN. The peaks around 2-Theta = 22.6° and 28.2° correspond to the T-Nb2O5 crystal phase, and the peaks around 2-Theta = 47.3° and 56.1° correspond to the Si crystal phase. Due to the high content of amorphous carbon, some of the diffraction peaks of Si and T-Nb2O5 are obscured.
[0083] like Figure 1 As shown in b, the Raman spectrum of Si / T-Nb2O5@C-CCNF shows the presence of silicon (504 cm -1 ), T-type niobium pentoxide (600cm -1 ) and the typical D peak of carbon materials (1340 cm -1 ) and G peak (1590cm -1 ), indicating that the composite material contains these three components at the same time. After calculation, the I D / I G The value is 1.07, indicating that the electrode contains a large amount of amorphous carbon, which brings a large number of defects and provides more reactive active sites.
[0084] pass Figure 1 a. Figure 1 The results shown in b all prove the successful preparation of Si / T-Nb2O5@C-CCNF in this example.
[0085] like Figure 2 As shown in Figure a, the XPS full spectrum analysis results show that there are five elements, C, N, O, Si, and Nb, in the sample, and the intensity of the C peak is much higher than that of the Nb and Si peaks, proving that Si / T-Nb2O5 is well coated in the carbon layer on the outer layer of the fiber.
[0086] like Figure 2 As shown in b, the three peaks in the HRXPS spectrum of C 1s are located at 284.7, 285.7 and 288.2 eV, corresponding to the CC bond, CO / CN bond and C=O bond, respectively. Among them, the CN bond strengthens the firmness of the carbon fiber. Figure 2 As shown in Figure c, the HRXPS spectrum of N 1s can be decomposed into three peaks, corresponding to pyridinic nitrogen (398.3eV), pyrrolic nitrogen (400.5eV) and graphitic nitrogen (401.8eV). Among them, pyridinic nitrogen can provide good electron donor / acceptor properties and can effectively participate in electron transfer. This characteristic can significantly improve the Faraday pseudocapacitance effect of the material; pyrrolic nitrogen has a faster charge diffusion characteristic, which can accelerate the conduction of charges, thereby improving the overall conductivity and electrochemical reaction rate of the material. At the same time, it can also form structural defects as active sites for lithium ion insertion. Graphitic nitrogen improves the conductivity of the composite material. As shown in Figure c, the HRXPS spectrum of N 1s can be decomposed into three peaks, corresponding to pyridinic nitrogen (398.3eV), pyrrolic nitrogen (400.5eV) and graphitic nitrogen (401.8eV). Figure 2 As shown in Figure d, in the HRXPS spectrum of O1s, the three peaks at 530.3eV, 532.2eV and 535eV can be attributed to Nb-O, Si-O and CO bonds. Figure 2 As shown in e, in the HRXPS spectrum of Si 2p, the three peaks at 99eV, 101eV and 103.5eV correspond to Si-Si, SiOx and SiO2 respectively, where SiO2 is produced by acid washing the nano-silicon particles with piranha solution. Figure 2 As shown in f, the HRXPS spectrum of Nb 3d shows two characteristic peaks at 207eV and 209eV, which are consistent with the 5+ 3d 5 / 2 and Nb 5+ 3d 3 / 2 Correspondingly, it is proved that Nb 5+ existence.
[0087] The above XPS test once again verified the successful preparation of Si / T-Nb2O5@C-CCNF.
[0088] like Figure 3 a. Figure 3 As shown in b, the sample Si / T-Nb2O5-P has a structure with a nano-silicon core (60-100nm) inside and a layer of short rod-shaped T-Nb2O5 (10-15nm) covering it. Figure 3 c. Figure 3 As shown in Figure d, the HRTEM results show lattice spacings of 0.31 nm and 0.39 nm, corresponding to the (111) crystal plane of Si and the (001) crystal plane of T-Nb2O5, respectively. Figure 3 e~ Figure 3As shown in h, the HAADF results show that the three elements Si, O, and Nb are evenly distributed, further proving the successful preparation of the short rod-like coating structure.
[0089] like Figure 4 a. Figure 4 As shown in Figure b, the SEM image of Si / T-Nb2O5@C-CCNF shows obvious fiber morphology, with a size of about 1 μm. The fiber surface is relatively smooth and there are no exposed particles, proving that Si / T-Nb2O5-P is well coated inside the carbon fiber. Figure 4 c~ Figure 4 Figure g shows the EDS image of a single fiber. The results show that the five elements C, N, O, Si, and Nb are evenly distributed along the fiber axis.
[0090] like Figure 5 a. Figure 5 As shown in b, the electrochemical impedance spectroscopy (EIS) test of the Si / T-Nb2O5@C-CCNF electrode before and after cycling was carried out. The test results show that the Si / T-Nb2O5@C-CCNF electrode has a relatively small charge transfer impedance (R ct ), is only 83.67Ω, which is because the construction of the mutually cross-linked nitrogen carbon fiber network structure provides a large number of charge transfer channels. -1 After 1000 cycles at the same current density, R ct It further decreases to 8.2Ω, which indicates that as the cycle progresses, the electrode sheet is activated and a large number of active sites provided by T-Nb2O5 are exposed, which promotes the transmission of lithium ions inside the electrode.
[0091] like Figure 6 a. Figure 6 As shown in b, the GITT results show that the Si / T-Nb2O5@C-CCNF electrode exhibits a higher lithium ion diffusion coefficient (3.07×10 -13 -1.05×10 -11 cm 2 S -1 ), indicating that T-Nb2O5 coating introduces more surface active sites, which enhances the lithium ion diffusion efficiency of the electrode. Faster lithium ion diffusion can reduce polarization and improve the charge and discharge capacity of the battery at high rates.
[0092] like Figure 7 a~ Figure 7 As shown in d, the Si / T-Nb2O5@C-CCNF electrode sheet was tested at 0.2A g using the Xinwei battery test system. -1 , 0.5A g -1 、1A g -1 , 2Ag -1The long cycle performance and rate performance under current density, the test results show that at 0.2Ag -1 After 480 cycles under the same conditions, the battery capacity is 1452 mAh g -1 The reversible specific capacity is 94.1%, and the capacity retention rate is 94.1%. -1 After 1000 stable cycles, the Si / T-Nb2O5@C-CCNF electrode still has a capacity of 644 mAh g -1 The high reversible specific capacity and capacity retention rate are 88.1%.
[0093] like Figure 8 a. Figure 8 As shown in b, the reaction is the rate performance test of Si / T-Nb2O5@C-CCNF electrode sheet at different current densities, and 0.2Ag was selected. -1 , 0.5Ag -1 , 1Ag -1 and 2Ag -1 The current density was set to 0.2A g after the test. -1 It can be seen that the Si / T-Nb2O5@C-CCNF electrode has a stable reversible specific capacity at different current densities, and the current density is reduced to 0.2Ag -1 After that, its reversible specific capacity also returned to 1400mAhg -1 The good rate performance and structural stability of the electrode material are attributed to the synergistic effect of T-Nb2O5 and the carbon fiber conductive network.
[0094] The T-Nb2O5 with small volume expansion in the core layer is coated on the Si surface, limiting the volume expansion of the internal Si, thereby preventing Si from falling off the electrode and ensuring the integrity of the electrode structure; at the same time, T-Nb2O5 has a unique tunnel and void structure, which can provide fast ion diffusion channels and contribute to better pseudocapacitance performance; the further coating of the nitrogen-doped carbon skin and the construction of the fiber conductive network structure improve the conductivity of the electrode material and introduce more active sites.
[0095] like Figure 9 a~ Figure 9 As shown in Figure e, the electrochemical reaction mechanism of the Si / T-Nb2O5@C-CCNF negative electrode material during the charge and discharge process was further analyzed and CV tests were performed on it. Figure 9 As shown in a, at 0.1mV S -1 At the scan rate, the first three cycles of CV scanning were performed on the half-cell assembled with Si / T-Nb2O5@C-CCNF and lithium sheet. In the first cycle of negative electrode scanning, the reduction peaks around 0.52V and 0.23V represent the formation of SEI and Lix The formation of Si alloy. Starting from the second cycle, the reduction peak near 0.52V disappears, proving that a relatively stable SEI is generated in the first cycle. In the positive electrode scan, the broad oxidation peak between 1-2V is due to the partially reversible reaction between SiO2 and the generated Li2Si2O5 and Si: 5SiO2+4Li + +4e+2Li2Si2O5+Si, this phenomenon occurs in SiO x More common in / C.
[0096] In order to further explore the electrochemical reaction kinetics of Si / T-Nb2O5@C-CCNF, the electrochemical reaction was carried out at different scan rates (0.2 mV S -1 , 0.4mV S -1 , 0.6mV S -1 , 0.8mV S -1 , 1mV S -1 ) under CV test, such as Figure 9 As shown in b. It can be seen that when the sweep rate is changed from 0.2mV S -1 Gradually increase to 1mV S -1 At the same time, due to the changes in the polarization and internal resistance of the electrode, the potentials of the positive and negative peaks in the CV curve move toward higher and lower potentials, respectively.
[0097] like Figure 9 As shown in d, when the sweep rate is changed from 0.2mV S -1 Increase to 1mV S -1 When the surface capacitance behavior contribution increases from 66% to 82.1%, according to previous studies, pseudocapacitive behavior is beneficial to the lithium ion storage behavior of electrode materials at higher current density. Therefore, the introduction of T-Nb2O5 enhances the pseudocapacitive effect of the electrode, thereby improving the rate performance and long cycle stability of the material.
[0098] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the description and implementation methods. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.
Claims
1. A method for preparing a core-core carbon fiber with T-Nb2O5 coated Si, characterized in that: The steps include: Step 1: After preparing the piranha solution, add the nano silicon powder, stir at room temperature and then freeze-dry to obtain the surface hydroxylated nano silicon powder; Step 2: After preparing a hydrated niobium oxalate solution and a polyvinyl pyrrolidone solution respectively, the surface hydroxylated nano-silicon powder is added to the polyvinyl pyrrolidone solution, and stirred to obtain a first solution, the hydrated niobium oxalate solution is added to the first solution and stirred to obtain a second solution, the second solution is subjected to a hydrothermal reaction and then freeze-dried, and calcined under an inert gas atmosphere to obtain a niobium pentoxide-coated nano-silicon structure; Step three, dissolve polyacrylonitrile and degas to obtain a third solution, dissolve polyvinyl pyrrolidone and polymethyl methacrylate, add the niobium pentoxide-coated nano-silicon structure and stir to obtain a fourth solution, add the third solution and the fourth solution into the coaxial electrospinning syringe respectively, push and collect the fiber membrane, vacuum dry and perform pre-oxidation treatment, and then perform carbonization treatment to obtain the core-loaded T-Nb2O5-coated Si skin-core structure carbon fiber.
2. The method for preparing a core-core carbon fiber with T-Nb2O5 coated Si as claimed in claim 1, characterized in that: In the step 2, 1 wt% to 5 wt% of niobium oxalate hydrate is dissolved in deionized water to prepare the niobium oxalate hydrate solution; Dissolving 5 wt % to 20 wt % of polyvinyl pyrrolidone in deionized water to prepare the polyvinyl pyrrolidone solution; as well as 1wt%-10wt% of the surface hydroxylated nano silicon powder is added into the polyvinyl pyrrolidone solution.
3. The method for preparing a core-core carbon fiber with T-Nb2O5 coated Si as claimed in claim 1 or 2, characterized in that: In the step 2, the temperature of the hydrothermal reaction is 200° C. and the time is 12 h; and The calcination temperature is 700° C. and the calcination time is 2 h.
4. The method for preparing a core-core carbon fiber with T-Nb2O5 coated Si as claimed in claim 3, characterized in that: In the step three, 10 wt % to 20 wt % of polyacrylonitrile is dissolved in 2-methylformamide and then degassed to obtain the third solution; and After dissolving 10wt%-20wt% of polyvinyl pyrrolidone and 1wt%-10wt% of polymethyl methacrylate in 2-methylformamide, 20wt%-50wt% of the niobium pentoxide-coated nano-silicon structure is added and stirred to obtain a fourth solution.
5. The method for preparing a core-core carbon fiber with T-Nb2O5 coated Si as claimed in claim 3, characterized in that: In the step 3, 10 wt% to 20 wt% of polyacrylonitrile is dissolved in 2-methylformamide until the solution is clear and transparent light yellow, and then the solution is allowed to stand at room temperature for degassing to obtain the third solution; and 10wt%-20wt% of polyvinyl pyrrolidone and 1wt%-10wt% of polymethyl methacrylate are dissolved in 2-methylformamide, and the solution is allowed to stand at room temperature until it becomes clear and transparent. Then, acetone is added and stirred at room temperature. Then, 20wt%-50wt% of the niobium pentoxide-coated nano-silicon structure is added and stirred to obtain a fourth solution.
6. The method for preparing a core-core carbon fiber with T-Nb2O5 coated Si as claimed in claim 4 or 5, characterized in that: The third solution and the fourth solution were added into the coaxial electrospinning syringe respectively, the high voltage was set to 14KV-18KV, and the propulsion speed of the third solution was 0.7-1.0mL h -1 The propulsion speed of the fourth solution is 0.1-0.3 mL / h -1 , the drum collection speed is 300rpm and the collection distance is 15cm.
7. The method for preparing a core-core carbon fiber with T-Nb2O5 coated Si as claimed in claim 6, characterized in that: In the step 3, the vacuum drying treatment is performed at a temperature of 60° C. for 4 hours; The pre-oxidation treatment is performed at a temperature of 230° C. for 2 hours; and The temperature of the carbonization treatment is 700° C. and the time is 2 h.
8. A core-loaded T-Nb2O5 coated Si skin-core structure carbon fiber, characterized in that: It is prepared using the method for preparing Si-coated skin-core structured carbon fiber with core-loaded T-Nb2O5 as described in any one of claims 1 to 7.
9. Application of a core-loaded T-Nb2O5 coated Si skin-core structure carbon fiber in a lithium-ion battery negative electrode, characterized in that: Use the skin-core structure carbon fiber with core-loaded T-Nb2O5 coated with Si as described in claim 8.
10. The use of the core-loaded T-Nb2O5 coated Si skin-core structure carbon fiber in the negative electrode of a lithium ion battery as claimed in claim 9, characterized in that: The core-loaded T-Nb2O5-coated Si-skin-core structured carbon fiber is cut and assembled into a lithium half-cell.
Citation Information
Patent Citations
Lithium ion battery anode material, and preparation method thereof
CN106571451A
Preparation method of lithium-ion battery Si@Nb2O5 composite anode material
CN109755509A
Lithium ion self-supporting silicon-carbon composite nanofiber negative electrode material and preparation method and application thereof
CN116516522A
